Daya Hambat Asap Cair Tongkol Jagung Terhadap Bakteri Kontaminan Pada Tuna Loin Segar Diasosiasikan Dengan Kadar Histamin Dan TVB-N - Naiu, Asri Silvana; Syah, Nabila Kamila (Jambura Fish Processing Journal, 2024)
The objective of this study is to analyse the inhibitory power of liquid smoke derived from corn cobs (Zea mays L.) at different levels of distillation on bacterial contaminants in fresh tuna (Thunnus sp) loins, which are associated with histamine levels and TVB-N values. The treatment in this research was the level of liquid smoke distillation, namely 3 times distillation, 2 times distillation, and 1 time distillation. The parameters tested included the inhibitory power of liquid smoke against bacteria, histamine levels, and TVB-N values, which were tested at the 18th hour at room temperature. This research was designed using the Completely Randomized Design (CRD) method. Data analysis used ANOVA and further tested with BNT. The research results demonstrated that the level of liquid smoke distillation had a significant influence (p5%) on all test parameters. The histamine levels produced ranged from 23,68 ppm to 46,18 ppm, while the TVBN values were in the range of 7,77mgN/100g to 11,05mgN/100g. Both were still in accordance with the SNI for Fresh Tuna Loin (2018). The greater the degree of distillation of liquid smoke, the more pronounced the inhibitory effect on bacteria and the greater the potential to inhibit bacterial growth in tuna loin.